Fibrosis-associated hepatocarcinogenesis revisited: Establishing standard medium-term chemically-induced male and female models - Romualdo, Guilherme Ribeiro [UNESP]; Prata, Gabriel Bacil [UNESP]; da Silva, Tereza Cristina; Fernandes, Ana Angélica Henrique [UNESP]; Moreno, Fernando Salvador; Cogliati, Bruno; Barbisan, Luís Fernando [UNESP] (Public Library of Science (PLoS), 2018)
Hepatocellular carcinoma causes ~10% of all cancer-related deaths worldwide, usually emerging in a background of liver fibrosis/cirrhosis (70%-90% of cases). Chemically-induced mouse models for fibrosis-associated hepatocarcinogenesis are widely-applied, resembling the corresponding human disease. Nonetheless, a long time is necessary for the development of preneoplastic/neoplastic lesions. Thus, we proposed an early fibrosis-associated hepatocarcinogenesis model for male and female mice separately, focusing on reducing the experimental time for preneoplastic/neoplastic lesions development and establishing standard models for both sexes. Then, two-week old susceptible C3H/HeJ male and female mice (n = 8 animals/sex/group) received a single dose of diethylnitrosamine (DEN, 10 or 50 mg/Kg). During 2 months, mice received 3 weekly doses of carbon tetrachloride (CCl4, 10% corn oil solution, 0.25 to 1.50 μL/g b.wt.) and they were euthanized at week 17. DEN/CCl4 protocols for males and females displayed clear liver fibrosis, featuring collagen accumulation and hepatic stellate cell activation (α-SMA). In addition, liver from males displayed increased CD68+ macrophage number, COX-2 protein expression and IL-6 levels. The DEN/CCl4 models in both sexes impaired antioxidant defense as well as enhanced hepatocyte proliferation and apoptosis. Moreover, DEN/CCl4-treated male and female developed multiple preneoplastic altered hepatocyte foci and hepatocellular adenomas. As expected, the models showed clear male bias. Therefore, we established standard and suitable fibrosis-associated hepatocarcinogenesis models for male and female mice, shortening the experimental time for the development of hepatocellular preneoplastic/neoplastic lesions in comparison to other classical models.